Pembelajaran Berbasis Masalah Berbantuan Kartu Jawaban Bersambung untuk Meningkatkan Hasil Belajar Fisika di SMA Negeri 10 Mataram - Widianta, I Made Narta (UNDIKMA, 2021)
This study aims to improve physics learning outcomes in the knowledge aspect through the application of Problem Based Learning assisted with Continuous Answer Cards. This research method used classroom action research. The subjects of this study were students of class X MIPA 2 SMAN 10 Mataram consisting of 26 people. The technique of collecting data on the results of learning physics uses a written test which is carried out through daily tests. The data analysis technique of this research was carried out descriptively. The results showed that there was an increase in the students' physics learning outcomes compared to their pre-cycle scores by 27% in the first cycle, 56% in the second cycle and 80% in the third cycle. The average value of students' physics learning outcomes increased, namely 51 in the pre-cycle, 54 in the first cycle, 66 in the second cycle, and 72 in the third cycle. The percentage of classical learning completeness with a KKM score of 70 also increased, namely 30% in the pre-cycle to 38% in the first cycle then to 58% in the second cycle and to 70% in the third cycle. Thus it can be concluded that Problem Based Learning assisted by Continuous Answer Cards can improve learning outcomes of physics in the aspects of knowledge of class X MIPA 2 students of SMAN 10 Mataram.